Le care en éducation : de la séparation à l'agir en dialogue - Pierre Usclat
In this text we will establish that when school relies on the principle of autonomy, the teachers' pedagogical practice will embrace its dynamics. It actually is a matter of separating the pupil from any particularism. Now an ergological analysis of what happens in an educative situation will show that the pupil will yet set to work to assume his singular - and particular - dimension. We will then ask ourselves what a "pedagogical act" of the teachers can be, not at first trying that the pupil would be consistent with a universal taking him away from what he is, but working with this. Care, notably with the four phases of an action it suggests, will thus lead us to consider a pedagogical act by dialogue.